ANALISIS POLA REPRESENTASI DAN GAYA BELAJAR MAHASISWA FISIKA PADA MATERI KINEMATIKA - Ananingtyas, Ratika Sekar Ajeng; Puspitasari, Wahyu Dwi; Rohmiati, Dyah Palupi; Prawitasari, Prawitasari (Universitas Negeri Malang, 2024)
Physics problems tend to presented in one or some representation forms, such as verbal; visual; mathematic; graphic; etc. The consistency of representation using and concept understanding have strong relation, while learning style using by students gives big help to understand a concept too. The purpose of this research is to know relationship between representation pattern and VAK learning styles of physics’ undergraduate students in solving physics problems. Research has been done qualitatively in phenomenology type. Data was obtained from a quiz using 4 representation forms, interview, and questionnaire. The results of this research showed that representation pattern and learning styles using by students had well relation where most chose visual as the most preferred of both.